Performance of reinforced engineered cementitious composite square columns - Mohsen Dayyani; Alireza Mortezaei; Mohammad Sadegh Rohanimanesh; Jafar Asgari Marnani (Građevinar)
This paper investigates the effects of aspect ratio and fibre fraction on the failure of engineered cementitious composite (ECC) concrete columns. When subjected to cyclic load, these columns may fail due to the strain-hardening of longitudinal bars or the formation of dominant cracks. In this experiment, 11 ECC columns with fibre fractions between 0–1.5 % and aspect ratios from 3–7, as well as a single reinforced concrete column, were tested. The results showed that both aspect ratio and fibre fraction significantly impacted the failure paths observed. Additionally, the ECC columns exhibited a cumulative energy dissipation capacity approximately 100 % higher than that of the conventional concrete column.